Income Tax and Value Creation in Colombian Companies (2019)
ABSTRACT Financial literature has developed a theoretical framework on business management called Value Management, this topic has not yet been accounted for economic and monetary policies as a key factor to establish the convenience and effects of tax related decisions over business value creation. The aim of the research is to evaluate the economic and financial impact of income tax on business value creation of Colombia´s Stock Exchange companies (BVC, “Bolsa de Valores de Colombia” in Spanish) within a five year period (2012-2017). The study was made using accounting metric tools through the event study methodology allowing to calculate the Cumulative Abnormal Return (CAR), and utilizing a multivariate regression model with the dependent variable CAR and the independent variables EVA, P/E, ROE and EPS. Income tax policies established during the study period in tax reforms had neither a direct nor a proportional effect on value generation.